Health Education About Contraception With Tiktok Media On The Level Of Knowledge Of Couples Of Childbearing Age In Choosing Contraception - Hairunnissa, Hairunnissa; Sagita, Diva (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: The purpose of this study was to determine whether there is an effect of health education through Tiktok video media on the knowledge of couples of childbearing age in choosing contraceptives. Methods: This study uses descriptive research with a case study approach method, with a total of 30 respondents who meet the predetermined inclusion criteria. Results: The results showed that there was an increase in the knowledge of couples of childbearing age in the selection of contraceptives, after health education was carried out, namely from a sufficient level of knowledge as many as 15 respondents (50%) to a good level of knowledge as many as 17 respondents (56%). Conclusions: From the results obtained, it can be concluded that there is an effect of health education through Tiktok video media on the knowledge of couples of childbearing age in the use of contraceptives.